PKM Kelompok KUPS Bamboe Wanadesa dalam Mengelola Ekowisata Bamboe Wanadesa Berbasis Digital - M. Miswaty; Misna Ariani; Anna Anganita Theresia Latumeten; Malik Anugrah; Prety Syahwa Nabilla (Lembaga Pengabdian Kepada Masyarakat, Universitas Warmadewa, 2024)
Bamboe Wanadesa Tourism is a nature-based tourism driven by the community around Pati village in Karang Joang sub-district, North Balikpapan sub-district. The aim of this community partnership program activity of HIBAH DRTPM 2024 is to utilize existing natural potential to become a tourist attraction that is well managed and known to the wider community through digital marketing and creating alternative economic potential as a member's economic resource so that it can improve the member's economy to become prosperous. The community partnership empowerment activity method is carried out with direct assistance by the implementation team and assisted by two students. Activities begin with preparations such as determining a schedule and preparing measurement instruments to carry out pre- and post-activity evaluations. The training carried out during PKM is management for tourism, training in making bamboo leaf cookies and bamboo leaves tea, financial reporting training, website and social media management training. The PKM Team evaluated the participants regarding their level of understanding of the training material. The results of the evaluation of understanding of the material showed that after receiving the training, the participants really understood and felt capable of implementing the training results. The Balikpapan University PKM team has handed over production equipment for making bamboo leaf cookies and bamboo leaf tea to partners as well as a playground to support tourist attraction facilities.